Implementasi good corporate governance, whistleblowing system dan risiko sanksi pajak terhadap kepatuhan wajib pajak - Sulistyowatie, Syska Lady; Pahlevi, Reza Widhar (CV. Kurnia Grup, 2023)
Tax compliance still needs to be improved by encouraging the implementation of transparent taxation, namely the transparency of tax management in all areas, both administrative and management of the use of funds derived from tax revenue. The real effort that must be done to implement the transparency is through the bureaucracy reform movement in the service system and tax administration that is through the implementation and implementation of Good Governance. Good governance is a well-executed organizational governance, by carrying out the principles of openness, justice and accountability in order to achieve the goals of the organization. The problems that will be studied by the researcher is a social and dynamic problem. Therefore, the researcher chooses to use quantitative research method to determine how to find, collect, process and analyze the data of the research result, so that this research is expected to give input for the need of strengthening of harmony between Good Corporate Governance and Whistleblowing System and the need to create system or policies and operational procedures of taxation sanction risk required for tax compliance implementation. The results showed that there is influence between the implementation of Good Corporate Governance to tax compliance, there is influence between Whistleblowing System on tax compliance, there is influence between Taxation Sanction on tax compliance.